2011
DOI: 10.1097/brs.0b013e3182011f84
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of 254 Patients After Manifestation of Spinal Metastases

Abstract: According to this analysis, the Bauer and the Bauer modified scores are the most reliable systems for predicting survival. Since the Bauer modified score furthermore consists of only four positive prognostic factors, we emphasize its impact and simplicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
93
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(104 citation statements)
references
References 26 publications
10
93
0
1
Order By: Relevance
“…We agree with Wibmer et al [12] that the primary tumor classifications are not up to date. However, based on survival data in this study, the conclusion that patients suffering from kidney cancer have a prognosis comparable to those with breast cancer cannot be followed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We agree with Wibmer et al [12] that the primary tumor classifications are not up to date. However, based on survival data in this study, the conclusion that patients suffering from kidney cancer have a prognosis comparable to those with breast cancer cannot be followed.…”
Section: Discussionsupporting
confidence: 93%
“…If a patient is considered fit enough to undergo metastasectomy, survival will most likely be prolonged based on their general condition and not the removal of the visceral metastasis. A recent retrospective study of 504 breast cancer patients irradiated for metastatic spinal cord compression by Rades et al [13] also found a strong negative effect on survival if visceral metastases were present, similar to Wibmer et al [12], Yamashita et al [14] and Crnalic et al [15].…”
Section: Discussionmentioning
confidence: 58%
“…In both situations, there is wide variation in prognostic factors. We found similar survival in patients treated with surgery plus RT and in those treated with RT alone 5,6,26 .…”
Section: Discussionsupporting
confidence: 61%
“…However, every score, even with its particu larities, requires complete evaluation of the systemic disease, including a histological diagnosis. Several authors have demonstrated that the primary tumor site is the most important prog nostic factor for patient survival, and this is well accepted 19 . However, in vertebral metastasis with spinal cord compres sion, there is an urgent need for decisionmaking, and the histo logical diagnosis and tumor staging data require time that is not available before treatment 7 .…”
Section: Discussionmentioning
confidence: 93%